Electrospun ZnO Nanowire Plantations in the Electron Transport Layer for High-Efficiency Inverted Organic Solar Cells - Elumalai, Naveen Kumar; Tan, Mein Jin; Vijila, Chellappan; Rajan, Jose; Suresh Kumar, Palaniswam; Sundaramurthy, Jayaraman; Hemant, Kumar Raut; Seeram, Ramakrishna (American Chemical Society, 2013)
Inverted bulk heterojunction organic solar cells having device structure ITO/ZnO/poly(3-hexylthiophene) (P3HT):[6,6]-phenyl C61 butyric acid methyl ester (PCBM) /MoO3/Ag were fabricated with high photoelectric conversion efficiency and stability. Three types of devices were developed with varying electron transporting layer (ETL) ZnO architecture. The ETL in the first type was a sol–gel-derived particulate film of ZnO, which in the second and third type contained additional ZnO nanowires of varying concentrations. The length of the ZnO nanowires, which were developed by the electrospinning technique, extended up to the bulk of the photoactive layer in the device. The devices those employed a higher loading of ZnO nanowires showed 20% higher photoelectric conversion efficiency (PCE), which mainly resulted from an enhancement in its fill factor (FF). Charge transport characteristic of the device were studied by transient photovoltage decay and charge extraction by linearly increasing voltage techniques. Results show that higher PCE and FF in the devices employed ZnO nanowire plantations resulted from improved charge collection efficiency and reduced recombination rate.